An exceptionally rare case of a diffuse midline glioma with concomitant H3.1 K27M and G34R mutations in the HIST1H3C (H3C3) gene - Zita Reisz; Rita Pereira; Smitha Nevis; Alan Mackay; Leena Bhaw; Yura Grabovska; Ross Laxton; Valeria Molinari; Anna Burford; Barnaby Clark; Cristina Bleil; Bassel Zebian; et al. (Acta Neuropathologica Communications)
Abstract Histone mutations (H3 K27M, H3 G34R/V) are molecular features defining subtypes of paediatric-type diffuse high-grade gliomas (HGG) (diffuse midline glioma (DMG), H3 K27-altered, diffuse hemispheric glioma (DHG), H3 G34-mutant). The WHO classification recognises in exceptional cases, these mutations co-occur. We report one such case of a 2-year-old female presenting with neurological symptoms; MRI imaging identified a brainstem lesion which was biopsied. Histology showed diffusely infiltrating pleomorphic astrocytes, multinucleated cells, and conspicuous mitotic activity; the diagnosis was DMG, H3 K27-altered (immunohistochemistry: H3K27me3 loss, H3K27M positivity). DNA methylation profiling (Illumina EPIC BeadArrays, brain tumour classifier (MNP v12.5 R package)) classified the tumour as ‘DMG, H3 K27-altered’ (calibrated score = 0.99). Further molecular studies (whole exome, whole genome sequencing) revealed concurrent H3.1 K27M and G34R mutations (clonal, in the same reads) of H3C3, FGF11 and PIK3CA somatic variants, and a pathogenic germline NBN variant. The RNAseq profile clustered with H3K27M-mutant tumours. A patient-derived cell culture was established enabling unbiased in vitro drug screening; no selective sensitivities were identified. Chromatin immunoprecipitation assays with sequencing (ChIP-seq; H3K27ac, H3K27me3, H3K36me3, RNApol2 marks) showed features in keeping with DMG H3 K27M-mutant tumours (H3K27ac loci including OLIG2, IRX1/2, PKDCC). The patient was treated with adjuvant radiotherapy, but progressed and passed away 13 months post-diagnosis. This case is an exceptionally rare, complex variant of histone-mutant paediatric HGG, illustrating that the H3.1 K27M mutation demonstrates a dominance over the molecular and clinical profiles compared to G34R, and highlights the importance of broad molecular profiling to identify such examples for further study.